Perilaku Petugas Terhadap Inovasi Sistem Informasi Kesehatan di Rumah Sakit Kanker Dharmais - Hairun Nisa; Daniel Happy Putra; Puteri Fannya; Lily Widjaja (Jurnal Komputasi, 2024)
Dharmais Cancer Hospital has implemented a SIMRS called SIMpel since 2016. The application has been successfully applied to computer systems used by various medical record service units, including admission, filling, coding, and reporting. However, in the implementation of the existing SIMRS, there are still challenges and barriers related to user adoption. So a study was conducted related to the evaluation of the use of SIMRS at Dharmais Cancer Hospital. The purpose of this study is to identify various elements that influence the acceptance of SIMRS among officers in order to increase their level of consistency and commitment in using SIMRS. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was used as the theoretical framework for this study. This study uses inferential analysis, with a total sample size of 58 respondents and the test used is the chi-square test. Based on the results of the analysis, it was found that there is a relationship between the constructs of performance expectancy, effort expectancy, and social influence with interest in using SIMRS. In addition, facilitating conditions were found to have a relationship with usage behavior. It can be concluded that there is a correlation between officers' acceptance and usage attitudes towards SIMRS for each construct in the UTAUT model. Therefore, it is necessary to maintain the interest and usage behavior of SIMRS at Dharmais Cancer Hospital while maintaining the quality of the system.